Work your stars : using astrology to navigate your career path, shine on the job, and guide your business decisions - Abergel, Matthew (New York Simon & Schuster, 1999)
Profiles the twelve signs of the Zodiac as they affect business matters, career choices, and dealing with different types of personalities on the job
One Spirit, 1/2000
Keywords: Asteology and business; Success in business--Miscellanea